Effects of continuous and pulsating water jet on CNT/concrete composite - Foldyna, Vladimir (Strojniški vestnik, 2017)
This paper presents first results of the study of the resistance of carbon nanotube concrete composite (CNT/concrete composite) to the action of continuous and pulsating water jets. The experiments oriented at the determination of erosion effects of pulsating and continuous water jets impinging the surface of reference (concrete) and CNT/concrete composite samples were performed. Tested samples were characterized by X-ray powder diffraction and scanning electron microscope. Samples were exposed to pulsating and continuous water jets at various operating parameters. Erosion effects of pulsating and continuous jets were evaluated in terms of material removal rate. The possible influence of addition of CNTs to the concrete on its resistance to the action of continuous and pulsating water jets is discussed in the paper. The experiments proved that CNT/concrete composite exhibits higher resistance than reference concrete to the action of both pulsating and continuous water jet under the given testing conditions.
Keywords: betonski kompozit; kontinuirani vodni curek; odnašanje materiala; ogljikove nanocevke (CNT); pulzirajoči vodni curek